Improving recycling markets - Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development, 2006)
Markets for many classes of potentially recyclable materials are growing. However, market failures and barriers are constraining some markets. Factors such as information failures, technological externalities, and market power can affect the prices, quantity, and quality of materials traded. This report presents the case for the use of industrial policies which address such market failures and barriers and these policies are seen as complements to more traditional environmental policies. Indeed, encouraging ever-higher recycling rates in the absence of such complementary measures may impose very high social welfare costs. This publication covers in particular the markets for waste oils, waste plastics, and used rubber tires.--Publisher's description
Introduction and overview of market failures and barriers -- Improving markets for waste oils -- Improving markets for waste plastics -- Improving markets for used rubber tyres -- Public policy and recycling markets
Includes bibliographical references
Keywords: Recycling (Waste, etc.); Recycled products